2022
DOI: 10.1155/2022/6235857
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Kohl (Surma) and Erythromycin in Treatment of Blepharitis: An Open-Label Clinical Trial

Abstract: Introduction. Blepharitis is a common and chronic form of eyelid inflammation. Blepharitis treatment aims to decrease symptoms through antibacterial effects. One of the most common treatments of eyelid diseases in traditional medicine is using kohl. This clinical trial aimed to investigate its efficacy as a complementary treatment in staphylococcal blepharitis through an open-label clinical trial. Materials and Methods. Thirty patients were randomized to receive kohl in one eye contralateral and erythromycin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…These results were confirmed through in vitro examination by observing the inhibition zone diameter of 17 mm against K. pneumoniae isolate. In a previous clinical trial study by Karbassi et al 19 from Iran, which was conducted on 30 patients with staphylococcal blepharitis, the efficacy of kohl in the treatment of blepharitis was significantly higher than that of erythromycin ointment. In another study by Al-Kaff et al 20 from Saudi Arabia, certain mixtures of kohl showed slight antimicrobial effects against Proteus , Staphylococcus , and Streptococcus strains.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These results were confirmed through in vitro examination by observing the inhibition zone diameter of 17 mm against K. pneumoniae isolate. In a previous clinical trial study by Karbassi et al 19 from Iran, which was conducted on 30 patients with staphylococcal blepharitis, the efficacy of kohl in the treatment of blepharitis was significantly higher than that of erythromycin ointment. In another study by Al-Kaff et al 20 from Saudi Arabia, certain mixtures of kohl showed slight antimicrobial effects against Proteus , Staphylococcus , and Streptococcus strains.…”
Section: Discussionmentioning
confidence: 90%
“…Investigating the chemical composition of kohl can explain its antibacterial and anti-inflammatory properties. An examination of the chemical components of kohl has revealed that the primary elements are zinc, antimony, carbon, sulphur, and iron 19 . The use of kohl leads to an increase in nitric oxide production, which has antimicrobial capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found that following lifestyle recommendations of Persian medicine decreases the gastrointestinal symptoms of vitiligo patients [8]. Also, one study on blepharitis patients showed the effectiveness of a Persian medicine formulation on blepharitis [9]. Also, different studies have evaluated the role of Persian medicine in depression [10], Insomnia [11], anorexia [12], etc.…”
Section: American Journal Of Biomedical Science and Research Am J Bio...mentioning
confidence: 99%